Penicillin Antibiotics in Modern Therapy: Efficacy, Safety, and Resistance Trends - Alanazi, Mashael Mannaa Bin Radhi; ‏Reem Alhamaidi Fahad Almutairi,; Fahd Omar amer Alsahafi,; Khalid Hamoud Alharbi,; Mohammed Fahad Alotaibi,; Hamad Bin Mohammed Bin Ali Aldawsari,; Mohammed Murdi Abdullah Alqahtani,; Al Anoud Abdullah Raheel Al Anzi,; Mahasen Fawaza Alharbi,; Watin Hutayl H. Al-Shammari,; Nazek Sufug Nazal Alenazi,; Mohammed Abdulrashid Abdulkarim Rajab,; et al. (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Penicillin, a cornerstone of β-lactam antibiotics, remains widely used for treating bacterial infections due to its broad activity and established safety profile. However, rising antimicrobial resistance and pharmacokinetic limitations necessitate careful therapeutic selection. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This review evaluates the clinical efficacy, safety, resistance trends, pharmacology, and administration considerations of penicillin in modern practice. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A comprehensive literature synthesis was conducted, analyzing FDA-approved indications, mechanisms of action, pharmacokinetics, adverse effects, drug interactions, and patient-specific considerations. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Penicillin retains effectiveness against gram-positive cocci, select gram-negative organisms, and anaerobes, with expanded-spectrum derivatives addressing resistance challenges. FDA-approved uses include anthrax, syphilis, meningitis, and streptococcal infections. Mechanistically, penicillin inhibits peptidoglycan cross-linking via irreversible binding to penicillin-binding proteins, leading to bacterial lysis. Pharmacokinetics reveal oral acid stability for penicillin V, while parenteral formulations ensure systemic exposure for penicillin G. Adverse effects range from mild gastrointestinal symptoms to severe hypersensitivity and rare neurotoxicity. Resistance, primarily mediated by β-lactamase production and altered permeability, underscores the need for β-lactamase inhibitors and stewardship strategies. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Despite resistance concerns, penicillin remains integral to antimicrobial therapy when guided by susceptibility testing and individualized dosing. Its favorable safety profile supports use in pregnancy, pediatrics, and lactation, provided contraindications are excluded. Interprofessional collaboration and patient education are essential to optimize outcomes and minimize complications.